Pengembangan Media Pembelajaran Berbasis Android Berbantuan Web Kodular untuk Materi Ikatan Kimia Kelas XI SMA/MA Sederajat - Saputri Nurfalah; Lenny Anwar S; Rasmiwetti Rasmiwetti (Lembaga Yasin AlSys, 2026)
The development of digital technology has had a major influence on the field of education, particularly in improving the quality of learning through the use of digital media. The use of Android-based learning media is one relevant alternative because smartphones have become part of students’ daily activities. In chemistry learning, chemical bonding material is often considered difficult to understand because it contains abstract concepts that cannot be observed directly, so learning media are needed that can visualize concepts more concretely and interactively. This study aims to develop Android-based learning media assisted by Web Kodular on chemical bonding material for Grade XI senior high school/Islamic senior high school or equivalent that is valid and obtains good user responses. This study used the Research and Development (R&D) method with a modification of the 4D development model into three stages, namely definition, design, and development. The developed product was validated by material validators, pedagogical validators, and media validators. The assessed aspects included content feasibility, presentation feasibility, instructional feasibility, language feasibility, technical quality, instructional communication media, and effects on learning strategies. Subsequently, one-to-one trials were conducted with three students of different ability levels, along with user response testing involving teachers and students. The results showed that the Android-based learning media assisted by Web Kodular on chemical bonding material were declared valid based on the results of material, pedagogical, and media validation. In addition, user responses to the developed media were in the very good category. Teachers gave positive responses regarding the aspects of learning media use, media display, clarity of presentation, and motivation, whereas students gave positive responses regarding ease of use and navigation, display, material, and motivation. The conclusion of this study affirms that Android-based learning media assisted by Web Kodular are feasible for use as chemistry learning media on chemical bonding material for Grade XI senior high school/Islamic senior high school or equivalent.